2022
DOI: 10.3390/math10132161
|View full text |Cite
|
Sign up to set email alerts
|

Uncertain Data Envelopment Analysis for Cross Efficiency Evaluation with Imprecise Data

Abstract: Self evaluation and peer evaluation in data envelopment analysis (DEA) are effective means to comprehensively reflect the efficiencies of decision-making units (DMUs). However, when some of the inputs and outputs of DMUs cannot be accurately observed, the traditional evaluation methods will lose their applicability. This paper attempts to treat the imprecise inputs and outputs as uncertain variables based on uncertainty theory and hence to propose a new uncertain DEA model for cross-efficiency evaluation via t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…This is where uncertainty modeling techniques, such as uncertainty theory, play a vital role. Uncertainty theory is a mathematical framework that deals with the modeling and quantification of uncertainty in various domains [ 81 , 82 , 83 , 84 , 85 , 86 ]. It provides concepts, methods, and techniques to represent, analyze, and reason with uncertain information.…”
Section: Uncertainty Theorymentioning
confidence: 99%
“…This is where uncertainty modeling techniques, such as uncertainty theory, play a vital role. Uncertainty theory is a mathematical framework that deals with the modeling and quantification of uncertainty in various domains [ 81 , 82 , 83 , 84 , 85 , 86 ]. It provides concepts, methods, and techniques to represent, analyze, and reason with uncertain information.…”
Section: Uncertainty Theorymentioning
confidence: 99%
“…In the calculation results of model (15), multiple DMUs' efficiency values may simultaneously be 1, which is not conducive to sorting the DMU set. In order to further study the ranking of efficient DMUs, the uncertain super-efficiency generalized DEA model is proposed as follows:…”
Section: 2mentioning
confidence: 99%
“…is added in model (15), each DMU has the same α-efficiency assessment result as the uncertain CCR model. Through this example, it is shown that by different α values, the basic uncertain DEA models can be expressed in a uniform way by the uncertain generalized DEA model.…”
Section: 1mentioning
confidence: 99%
See 1 more Smart Citation